2018
DOI: 10.1007/s10554-018-1390-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different treatment strategies on left ventricular myocardial deformation parameters in patients with chronic renal failure

Abstract: The aim of this study was to compare left ventricular (LV) functions by speckle tracking echocardiography (STE) in chronic kidney disease (CKD) patients in various stages and under different renal replacement treatments in order to evaluate possible differences between them. This prospective study included 150 patients with CKD. Renal transplantation patients with glomerular filtration rate greater than 60 ml/min/1.73 m, patients receiving hemodialysis three times a week, and patients in the predialysis stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…Significant apicobasal gradient (overrotation of the LV apex) suggesting a compensating mechanism could also be detected in these cases similarly to what happens during stress (24). In post-KTx patients, ESRD-related consequences could explain our findings, but the effect of surgical treatment could not be excluded either (18). Further studies are warranted to confirm our findings and to compare them to renal and other functional parameters.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Significant apicobasal gradient (overrotation of the LV apex) suggesting a compensating mechanism could also be detected in these cases similarly to what happens during stress (24). In post-KTx patients, ESRD-related consequences could explain our findings, but the effect of surgical treatment could not be excluded either (18). Further studies are warranted to confirm our findings and to compare them to renal and other functional parameters.…”
Section: Discussionsupporting
confidence: 59%
“…To this point, however, there is limited information on the relationship between CKD, KTx and LV rotational mechanics. According to Yildirim et al LV rotational and twist parameters did not differ between those of predialysis and transplantation patient groups (18). In contrast, Deng et al found that LV basal and apical rotations, average twist and torsion were higher following successful KTx as compared to pre-KTx results (19).…”
Section: Discussionmentioning
confidence: 95%
“…18 The same has been described in adults and children exposed to anthracyclines. 19-21 A decreased longitudinal strain has been reported to be a significant risk factor for all-cause mortality in adults with ESRD, 22 whereas the impairment in renal function as demonstrated by the estimated glomerular filtration rate (eGFR) has been reported to be linked to the decline in strain values, 23,24 and our study aimed to detect the early changes in myocardial mechanics and the occurrence of myocardial deformation in pediatric patients with ESRD using the STE as an imaging modality.…”
Section: Introductionmentioning
confidence: 99%
“…The leading causes of death in patients who died with a functioning allograft are CVDs as well (78) suggesting a compensating mechanism could also be detected in these cases similarly to what happens during stress (89). In post-KTx patients, ESRD-related consequences could explain our findings, but the effect of surgical treatment could not be excluded either (85). Further studies are warranted to confirm our findings and to compare them to renal and other functional parameters.…”
Section: Left Ventricular Rotational Abnormalities Following Successfmentioning
confidence: 63%
“…Other variables including global longitudinal strain and diastolic dysfunction were not found to be improved significantly(82).It is known that LV twisting mechanism is affected by several conditions and disorders, but the results are conflicting(75,83,84). To this point, however, there is limited information on the relationship between chronic kidney disease (CKD), KTx and LV rotational mechanics.According to Yildirim et al LV rotational and twist parameters did not differ between those of predialysis and transplantation patient groups(85). In contrast, Deng et al found that LV basal and apical rotations, average twist and torsion were higher following successful KTx as compared to pre-KTx results(86).…”
mentioning
confidence: 95%